Preparation of Carboxymethyl Cellulose-Based Macroporous Adsorbent by Eco-Friendly Pickering-MIPEs Template for Fast Removal of Pb2+ and Cd2+ - Wang, Feng; Zhu, Yongfeng; Xu, Hui; Wang, Aiqin (Frontiers in Chemistry, 2019)
Recently, Pickering high internal phase emulsions (Pickering HIPEs) has been widely used to fabricate macroporous materials. However, the high usage of poisonous organic solvent in HIPEs not only greatly increase the cost but also is harmful to human health and environment, which lead to the limited large-scale applications. In this study, we prepared a novel monolithic macroporous material of carboxymethyl cellulose-g-poly(acrylamide)/montmorillonite (CMC-g-PAM/MMT) by the free radical polymerization via the oil-in-water Pickering medium internal phase emulsions (Pickering MIPEs), which used the non-toxic and eco-friendly flaxseed oil as continuous phase, MMT and Tween-20 (T-20) as stabilizer. The pore structure of the resulting macroporous materials could be tuned easily by adjusting the content of MMT, co-surfactant T-20 and the oil phase volume fraction. The maximal adsorption capacities of the prepared macroporous material for Pb2+ and Cd2+ are 456.05 mg/g and 278.11 mg/g respectively, and the adsorption equilibrium can be reached within 30min. Otherwise, the macroporous monolith exhibited excellent reuseability through five adsorption-desorption cycles. Thus, the eco-friendly Pickering-MIPEs is a potential alternative method to be used to fabricate multi-porous adsorption materials for environmental applications.